2016
DOI: 10.1080/13506285.2017.1289997
|View full text |Cite
|
Sign up to set email alerts
|

Facelikeness matters: A parametric multipart object set to understand the role of spatial configuration in visual recognition

Abstract: There is a view that faces and objects are processed by different brain mechanisms. Different factors may modulate the extent to which face mechanisms are used for objects. To distinguish these factors, we present a new parametric multipart three-dimensional object set that provides researchers with a rich degree of control of important features for visual recognition such as individual parts and the spatial configuration of those parts. All other properties being equal, we demonstrate that perceived faceliken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…These observations indicate that, all other things being equal, perceived face‐likeness plays a role in the magnitude of the EEG individuation response. This finding also illustrates how the adult visual recognition system exploits familiar spatial configurations when learning new object categories (Lochy et al., 2017; see also Vuong et al., 2017).…”
Section: Advantages Of the Approachsupporting
confidence: 62%
See 1 more Smart Citation
“…These observations indicate that, all other things being equal, perceived face‐likeness plays a role in the magnitude of the EEG individuation response. This finding also illustrates how the adult visual recognition system exploits familiar spatial configurations when learning new object categories (Lochy et al., 2017; see also Vuong et al., 2017).…”
Section: Advantages Of the Approachsupporting
confidence: 62%
“…Note that finding a significant individuation response for non‐face object categories would not at all undermine the validity of the approach to measure FI, as long as the neural individuation responses are quantitatively and qualitatively different for facial identity (if physical similarity between oddball and base exemplars is matched across designs). In this context, Lochy et al (2017) tested participants undergoing weeklong training with novel multipart objects (Vuong et al., 2017) and found large individuation responses for exemplars at bilateral occipital sites, but without right hemispheric lateralization. Interestingly, one group of participants instructed to explicitly individuate the objects in a “face‐like” stimulus orientation showed an increase in the EEG individuation responses after training.…”
Section: Advantages Of the Approachmentioning
confidence: 99%
“…According to a particular version of this view, this expert system would even be so flexible that it could become involved in adulthood for non‐face object shapes, for example, after learning to individualize these shapes for only a few hours (Gauthier & Tarr, ; Wong, Palmeri, & Gauthier, ). As discussed extensively in previous reviews (McKone, Kanwisher, & Duchaine, ; Rossion, ), but also demonstrated with cases of reported prosopagnosia (Rezlescu, Barton, PItcher, & Duchaine, ), this latter view does not hold (see also Lochy et al ., ; Vuong et al ., , for evidence that small learning effects attributed to visual expertise acquired in adulthood depend on stimulus facelikeness).…”
Section: Why Does the Visual Similarity Account Persist?mentioning
confidence: 99%
“…Giuseppe Arcimboldo, 1527Arcimboldo, -1593 or photographers (e.g., Robert & Robert, 1996), and even recently observed in nonhuman primates (Taubert et al, 2018;Taubert, Wardle, Flessert, Leopold, & Ungerleider, 2017;Taubert, Wardle, & Ungerleider, 2020). Perceiving a face in a nonface stimulus leads to several facelike processing advantages, such as improved individuation abilities (Vuong et al, 2017), or higher saliency in a visual search task (Keys, Taubert, & Wardle, 2021).…”
Section: Introductionmentioning
confidence: 96%